Sustainable Human Development - Sharif, Amin Faraj (Journal of Legal and Political Studies, 2015)
The purpose of this research is to focus on most prominent theoretical aspects related to human development, through understanding the core of the concept, historical progress and uncovering its developments and changes. Then, the research works on different dimensions of the concept, identifying its measurement methods. To implement this, the research uses both descriptive and explanatory methods. Finally, the research concludes that human development is emerged as an appropriate mechanism to keeping balance between achieving capacities and using them with enhancing and widening different choices to humans, as it is suggested by the many global reports of human development issued by United Nations for Development and also by the concept of sustainable development which advanced by environmentalists.
Keywords: Sustainable; Human Development; Sustainable Development; United Nations; Humans Rights